Food Security, and Health And Nutritional Status of Indian Women From Oil Palm Plantations in Negeri Sembilan, Malaysia - Mohamadpour Kldeh, Masoumeh (2004)
A cross sectional study was conducted to determine the relationship between food security and health and nutritional status among 169 Indian women (19- 49 years, non-pregnant and non-lactating) from selected oil palm plantations in Negeri Sembilan. The women were interviewed for socio-economic, demographic, physical activity, household food security and dietary intake information and measured for weight, height, waist circumference and blood pressure. Blood samples were collected from 147 women and analyzed for total cholesterol (TC), high-density lipoprotein-cholesterol (HDL-C), lowdensity lipoprotein-cholesterol (LDL-C), triglyceride (TG) and plasma glucose (FPG) levels. For data analysis, descriptive statistics, ANOVA and logistic regression were conducted. Using the Radimer/Comell Hunger and Food Insecurity Instrument, a majority of the households experienced household insecurity (24.9%), individual insecurity (19.5%) or child hunger (40.8%). About 39.1% and 26.0% of the women were overweight and obese, respectively. More than half (68.6%) of the women had at risk waist iv circumference (~ 88 cm). While 70.4% of the women were in the highly active category, 29.6% were either sufficiently active or insufficiently active. The mean intake of energy and most nutrients were lower than the recommended values. Similarty, the mean number of servings for all food groups was less than the recommended servings. The mean diet diversity score was 10.10 ± 10.00 (maximum=29) with most women (89.4%) had diet diversity less than 10. The percentages of women with TG~2.3 mmollL, TC~ 6.2mmoIlL, LDLC> 4.1 mmollL, HDL-C<1.03 mmollL, FPG~6.1 mmollL and BP~130/85 mmHg were 14.3%, 2.8%, 12.2%, 32%, 12.9% and 19.7%, respectively. There were significantly decreasing patterns in mean household income, income per capita, year of schooling, diet diversity, vitamin A intake and number of serving from meaUfishllegumes and increasing patterns in mean number of children and prevalence of women with at risk waist circumferences with severity of food insecurity (p<0.05). For physical activity, women experiencing household food insecurity significantly spent higher minutes/day (333.13 ± 178.36) for moderate activities than women in food secure and child hunger households. In addition, women experiencing household food insecurity significantly spent higher minutes/day (343.70 ± 185.65) for vigorous activities than child hunger households (p<0.05). There was no significant difference in TG, HDL-C, FPG and blood pressure by food security levels. The mean number of health risks was significantly higher in child hunger (2.27 ± 1.20) than in individual food insecure (1.48 ± 1.05) groups. While the prevalence of people with more than 3 health risks was highest in child hunger group (42.9%), a majority (82.4%) of food secure women had less than 3 health risks. The logistic regression showed that housewives, higher age, higher waist circumference, lower years of education and lower duration of physical activity significantly increased the risk for the women to have health problems. In addition, women who had higher intake of milk and dairy products, meatlfish/poultry/legumes and higher diet diversity were more likely to be protected against health problems. In the present study, the effect of food insecurity on health risks is through dietary intakes, which may have impact on waist circumference. As households become food insecure, the ability to obtain variety of foods will be compromised and consequently put the women at risk of having high waist circumference and other health problems. The present study showed that food insecurity among the Indian women from selected palm plantations is indirectly associated with poor health and nutritional status. Therefore, appropriate community-based intervention programs should be developed and implemented to address the problem of food insecurity and possible health and nutritional outcomes.